Designing Business Reputation Ecosystems — A Method for Issuing and Trading Monetary Ratings on a Blockchain - Hemmrich, Simon; Bobolz, Jan; Beverungen, Daniel; Blömer, Johannes (ECIS 2023 Research Papers)
Market transactions are subject to information asymmetry about the delivered value proposition, causing transaction costs and adverse market effects among buyers and sellers. Information systems research has investigated how review systems can reduce information asymmetry in business-to-consumer markets. However, these systems cannot be readily applied to business-to-business markets, are vulnerable to manipulation, and suffer from conceptual weak spots since they use textual data or star ratings. Building on design science research, we conceptualize a new class of reputation systems based on monetary-based payments as quantitative ratings for each transaction stored on a blockchain. Using cryptography, we show that our system assures content confidentiality so that buyers can share and sell their ratings selectively, establishing a reputation ecosystem. Our prescriptive insights advance the design of reputation systems and offer new paths to understanding the antecedents, dynamics, and consequences to reduce information asymmetry in B2B transactions.

On the impossibility of surviving (iterated) deletion of weakly dominated strategies in rational MPC - Blömer, Johannes; Bobolz, Jan; Bröcher, Henrik

A Generic Construction of an Anonymous Reputation System and Instantiations from Lattices - Blömer, Johannes; Bobolz, Jan; Porzenheim, Laurens Alexander

Privacy-Preserving Cryptography: Attribute-Based Signatures and Updatable Credentials - Eidens, Fabian

Cryptimeleon: A Library for Fast Prototyping of Privacy-Preserving Cryptographic Schemes - Bobolz, Jan; Eidens, Fabian; Heitjohann, Raphael; Fell, Jeremy

Issuer-Hiding Attribute-Based Credentials - Bobolz, Jan; Eidens, Fabian; Krenn, Stephan; Ramacher, Sebastian; Samelin, Kai (Cryptology and Network Security)

A Complexity Theoretical Study of Fuzzy K-Means - Blömer, Johannes; Brauer, Sascha; Bujna, Kathrin (ACM Transactions on Algorithms)

Privacy-Preserving Incentive Systems with Highly Efficient Point-Collection - Bobolz, Jan; Eidens, Fabian; Krenn, Stephan; Slamanig, Daniel; Striecks, Christoph (Proceedings of the 15th ACM Asia Conference on Computer and Communications Security (ASIA CCS ’20),)

How well do SEM algorithms imitate EM algorithms? A non-asymptotic analysis for mixture models - Blömer, Johannes; Brauer, Sascha; Bujna, Kathrin; Kuntze, Daniel (Advances in Data Analysis and Classification)

Cryptography for the Crowd — A Study of Cryptographic Schemes with Applications to Crowd Work - Löken, Nils